Phytoene Is More Efficiently Absorbed Than Lycopene by In Vitro Intestinal Cells but Is Absorbed and Cleared Similarly to Lycopene by In Vitro Prostate Cancer Cells. (14th June 2022) - Moran, Nancy; Alexander, Brianna; Johnson, Rachael; Hason, Noor
Abstract: Objectives: Consuming tomatoes and the tomato carotenoid lycopene (LYC) is epidemiologically associated with reduced prostate cancer risk. Tomato carotenoids, including LYC, phytoene (PE), and beta-carotene (BC), are found in human prostate tissue, with greater PE: LYC ratios found in the blood and prostate tissue relative to the diet. We tested the hypothesis that PE is more efficiently absorbed by prostate cells and by absorptive intestinal cells than LYC, explaining the enrichment of PE in blood and prostate tissue. Methods: In vitro prostate cancer (LNCaP, PC-3) and non-cancerous prostate epithelial (RWPE-1) cells were treated with human serum enriched with PE, LYC, BC, or control (final media concentration 1 uM) for 6 hours. Clearance of PE, LYC, and BC from LNCaP cells was monitored for 48 hours after a 16 hour pre-incubation with carotenoids (n = 5 trials). Differentiated in vitro absorptive intestinal cells (Caco-2 HTB-37 cultured 21 d on a permeable support) were treated with mixed lipid micelles and either PE, LYC, BC, or no carotenoid (final media carotenoid concentration 2 uM) for 4 or 24 h (n = 5 trials). Cell and media carotenoid concentrations were measured by HPLC-PDA. Results: PC-3s absorbed 3.8%, 1.9%, and 2.5% (not significantly different, ns) and LNCaP cells absorbed 1.5%, 2.6%, and 2.0% of the LYC, PE, and BC (ns) doses, respectively, while RWPE-1 cells absorbed more of the BC dose (8.7%) than the PE dose (0.4%, P < 0.05), and LYC dose absorption was intermediate and similar to both PE and BC (2.5%). LNCaP cells cleared PE at the same rate as BC and LYC over 48 h. Intestinal Caco-2 cells absorbed more PE dose at 4 and 24 h (16.3%, 10.8%) than LYC (0.6%, 0.9%, respectively) or BC (5.8%, 7.5% respectively) (P < 0.05), while the amount of carotenoid recovered in the basolateral media showed a similar, though non-significantly different, pattern. Conclusions: These results align with whole body pharmacokinetic findings suggesting that differences in intestinal absorption may be a key determinant in relative tissue carotenoid accumulation, and reveal that cancer versus non-cancer cell types may differ in carotenoid absorption characteristics. Funding Sources: NIH NCCIH/ODS R01 AT008576.